EKSPLORASI JENIS KATAK (KELAS: AMPHIBIA, ORDO ANURA) DI TAMAN NASIONAL GUNUNG RINJANI LOMBOK - I Gede Nano Septian (Program Studi Pendidikan Biologi, 2022)
Rinjani National Park is located at Lombok Island West Nusa Tenggara. Biogeographically Lombok Island is a part of the Lesser Sunda archipelago which included to the Wallacean subregion that have large biodiversity, one of them is amphibian. These study objectives are to contribute and consolide information about species description, distribution and habitat. The data was conducted using Visual Encounter Survey (VES) method. The amphibian of Rinjani National Park consist of nine species belonging to five families (two Bufonidae, four Dicroglossidae, one Microhylidae, one Ranidae, and one Rhacoporidae). Five species were aquatic (L. dammermani, L. kadarsani, F. cancrivora, F. limnocharis and H. florensis), four species were semi aquaticn(D. melanostictus, I. biporcatus, O. monticola, and P. leucomystax).